Eph/Ephrins-Mediated Thymocyte–Thymic Epithelial Cell Interactions Control Numerous Processes of Thymus Biology - García-Ceca, Javier; Alfaro, David; Montero-Herradón, Sara; Tobajas, Esther; Muñoz, Juan José; Zapata, Agustín G. (Frontiers in Immunology, 2015)
Numerous studies emphasize the relevance of thymocyte-thymic epithelial cell (TECs) interactions for the functional maturation of intrathymic T lymphocytes. The tyrosine kinase receptors Ephs (Erythropoietin-producing hepatocyte kinases) and their ligands, ephrins (Eph receptor interaction proteins), are molecules known to be involved in the regulation of numerous biological systems in which cell-to-cell interactions are particularly relevant. In the last years, we and other authors have demonstrated the importance of these molecules in the thymic functions and the T-cell development. In the present report, we review data on the effects of Ephs and ephrins, in the functional maturation of both thymic epithelial microenvironment and thymocyte maturation as well as on their role in the lymphoid progenitor recruitment into the thymus.